Nanodeserts: A Conjecture in Nanotechnology to Enhance Quasi-Photosynthetic CO2 Absorption - Wenfeng Wang; Xi Chen; Yifan Zhang; Jianjun Yu; Tianyi Ma; Zhihan Lv; Jing Zhang; Fanyu Zeng; Hui Zou (International Journal of Polymer Science)
This paper advances “nanodeserts” as a conjecture on the possibility of developing the hierarchical structured polymeric nanomaterials for enhancing abiotic CO2 fixation in the soil-groundwater system beneath deserts (termed as quasi-photosynthetic CO2 absorption). Arid and semiarid deserts ecosystems approximately characterize one-third of the Earth’s land surface but play an unsung role in the carbon cycling, considering the huge potentials of such CO2 absorption to expand insights to the long-sought missing CO2 sink and the naturally unneglectable turbulence in temperature sensitivities of soil respiration it produced. “Nanodeserts” as a reconciled concept not only indicate a conjecture in nanotechnology to enhance quasi-photosynthetic CO2 absorption, but also aim to present to the desert researchers a better understanding of the footprints of abiotic CO2 transport, conversion, and assignment in the soil-groundwater system beneath deserts. Meanwhile, nanodeserts allow a stable temperature sensitivity of soil respiration in deserts by largely reducing the CO2 release above the deserts surface and highlighting the abiotic CO2 fixation beneath deserts. This may be no longer a novelty in the future.